Immunogenicity of Bacillus Calmette-Guérin in pigs: potential as a translational model of non-specific effects of BCG - Jensen, Kristoffer Jarlov; Hansen, Mette Sif; Skovgaard, Kerstin; Svensson, Erik; Larsen, Lars Erik; Heegaard, Peter M. H.; Benn, Christine Stabell; Jungersen, Gregers (Frontiers in Immunology, 2023)
Clinical and immunological studies in humans show that the live attenuated Bacillus Calmette-Guérin (BCG) vaccine has beneficial non-specific effects, increasing resistance against diseases other than tuberculosis. The underlying mechanisms are currently being explored. The pig exhibits considerable physiological similarity to humans in anatomy and physiology, suggesting that similar responses to BCG could be expected. Studies of the non-specific effects of BCG in pigs are scarce. We investigated the feasibility of using pigs as a large animal model to investigate the non-specific immunological effects of BCG.In a series of experiments, we randomized newborn or young piglets from conventional farms to receiving BCG or placebo and investigated the persistence of live BCG bacteria in various tissues, the immunogenicity of BCG in ex vivo blood and in vitro stimulation assays, and the acute phase protein and clinical responses to heterologous infectious challenge with influenza A virus or Actinobacillus pleuropneumoniae.The BCG vaccine was generally well tolerated. In contrast to humans, no skin reaction in the form of abscesses, ulcers, or scars was observed. Live BCG was recovered from draining lymph nodes in 2/13 animals 20 weeks after vaccination. Specific in vitro responses of IFN-γ to antigen-specific re-stimulation with mycobacterial antigen were increased but not TNF-responses to TLR2 or TLR4 agonists. A few genes were differentially expressed in blood after vaccination, including the antiviral genes RIG-I and CSF1, although the effect disappeared after correction for multiple testing. Clinical symptoms after heterologous bacterial or viral respiratory infections did not differ, nor did virus copies in nasopharyngeal samples after the challenge. However, the acute phase protein response was significantly reduced in BCG-vaccinated animals after influenza challenge but not after A. pleuropneumoniae challenge.BCG was safe in pigs, inducing specific immunological responses, but our model did not corroborate the innate immunological responsiveness to BCG seen in humans. The dose of BCG or the bacterial and viral challenges may have been sub-optimal. Even so, the acute phase protein response to influenza infection was significantly reduced in BCG-vaccinated animals.